Dionysian triumph sarcophagi - Leveritt, William A.G. (2016)
This thesis explores the meanings of those Roman sarcophagi which show the Indian triumph of Dionysus. This group, found from approximately the early Antonine to just after the Severan period, shows the same mythological characters in similar positions and surroundings. They --- together with other groups --- tend to be approached from a methodology which either explicitly anticipates homogeneity of meaning or tacitly implies it through the transferral of interpretations from one piece to another. This study attempts to reconsider such actions by exposing the different effects that individual sarcophagi draw.